Paul Gilroy. The Black Atlantic: Modernity and Double Consciousness. London, Verso, 1993. 261p Paul Gilroy. Small Acts. Thoughts on the Politics of Black Cultures. Londres, Serpent’s Tail, 1993. 257p - Tomichi, Dale (Afro-Ásia, 1996)
.